GSM based flood warning system using FPGA / Wan Mohd Azim Wan Mohd Zubir - Wan Mohd Zubir, Wan Mohd Azim (2012)
Flood is one of the frequent natural disasters occur each year. It can occur due to heavy rain, dam outbreak or overflow water in the river. In other words, rivers can be one of the biggest causes of flood. By monitoring the condition of water level in river or drain, flood can be anticipated early and warnings can be delivered to public in order to prevent loss of property and life. GSM based Flood Monitoring and Warning System (FMWS) is proposed here to convey the condition of river or give warning to people at affected area. Any data received from water level and water flow rate meter is processed and delivered to main system before SMS notifications are sent to public. Currently most of GSM based applications are developed using microcontroller such as PIC or 8051 microcontroller. With the flexibility in designing the hardware, FPGA is chosen to be the heart of the system. An interface unit, UART, between GSM modem and FMWS controller is modeled using Quartus II software and implemented on the Altera DE2 Board.